2019
DOI: 10.1111/1756-185x.13731
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness and safety of additional administration of tacrolimus in rheumatoid arthritis patients with an inadequate response to abatacept: A retrospective cohort study

Abstract: Objective: Abatacept (ABT) demonstrates good clinical efficacy and retention in rheumatoid arthritis (RA) patients. However, no rescue treatment option against inadequate response to ABT exists. Since tacrolimus (TAC) and ABT suppress T lymphocytes via different mechanisms and a combination of these agents could potentially be effective, this study aimed to examine the efficacy and safety of add-on TAC therapy in RA patients with inadequate response to ABT. Methods:Of 550 patients treated with ABT and register… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…[ 22 , 27 ], revealing that TAC was good enough and well-tolerated in Japanese patients who were resistant to biologics. Furthermore, some Japanese authors have described the real-world effect of ABT/TAC combination therapy [ 28 , 29 ]. Fujibayashi et al reported that ABT/TAC, as well as ABT/MTX combination therapy, was effective in Japanese RA patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 22 , 27 ], revealing that TAC was good enough and well-tolerated in Japanese patients who were resistant to biologics. Furthermore, some Japanese authors have described the real-world effect of ABT/TAC combination therapy [ 28 , 29 ]. Fujibayashi et al reported that ABT/TAC, as well as ABT/MTX combination therapy, was effective in Japanese RA patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fujibayashi et al reported that ABT/TAC, as well as ABT/MTX combination therapy, was effective in Japanese RA patients [ 28 ]. Suzuki et al also reported that additional administration of TAC in RA patients who showed an inadequate response to ABT was effective [ 29 ]. Our study also showed that ABT/TAC combination therapy was effective in elderly as well as younger RA patients, leading to sustained remission rates and implicating a profound combination effect of ABT with TAC.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study involving 550 RA patients treated with abatacept, 25 inadequate responders underwent an add-on macrolide calcineurin inhibitor tacrolimus therapy. At week 24, 40.0% of patients achieved low disease activity or remission, and the EULAR moderate or good response was 72.0% ( 316 ).…”
Section: Bdmards Blocking T Cells Cd20 and Il-6rmentioning
confidence: 99%
“…Compared to other b/tsDMARDs, Abatacept (ABT), a novel T-cell costimulation modulator, created compelling clinical benefits and security in patients who did not respond to anti-tumor necrosis factor-α or methotrexate treatment[ 7 , 8 ]. However, ABT is not effective in all patients[ 9 ]. The poor response to ABT in D2T RA patients may be linked to inflammatory cytokines; however, the exact pathogenesis remains unknown.…”
Section: Introductionmentioning
confidence: 99%